2000
DOI: 10.1007/s004670050777
|View full text |Cite
|
Sign up to set email alerts
|

Acute cyclosporine A-induced nephrotoxicity: a rabbit model

Abstract: Chronic cyclosporine A (CsA) nephrotoxicity has been widely assessed but only few studies have described acute nephrotoxicity. As CsA is now used for short periods, we developed an experimental model of acute CsA-induced nephrotoxicity. Renal clearances of inulin and para-aminohippurate were assessed in 35 New Zealand rabbits. Group 1: control, no treatment; group 2: CsA 25 mg/kg per day in 0.5 ml/kg per day for 5 days; group 3: vehicle Cremophor-EL, 0.5 ml/kg per day for 5 days; group 4: follow-up, the same a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 8 publications
(11 reference statements)
5
26
1
Order By: Relevance
“…In the day 20 to 24 CsA group, the does suffered significantly during the second half of gestation and their weight gain was negligible. This indicated that physiologic changes occurring during the last one-third of gestation in rabbits were very sensitive to CsA (33), whereas CsA administration was demonstrated to have no effect on food intake and total weight gain among nonpregnant rabbits, even at twice the dose (23,34). This factor produced fetal growth retardation in the day 20 to 24 CsA group only.…”
Section: Csa Therapy and Pregnancy Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the day 20 to 24 CsA group, the does suffered significantly during the second half of gestation and their weight gain was negligible. This indicated that physiologic changes occurring during the last one-third of gestation in rabbits were very sensitive to CsA (33), whereas CsA administration was demonstrated to have no effect on food intake and total weight gain among nonpregnant rabbits, even at twice the dose (23,34). This factor produced fetal growth retardation in the day 20 to 24 CsA group only.…”
Section: Csa Therapy and Pregnancy Outcomesmentioning
confidence: 99%
“…First, rabbits exhibit a hemochorial type of placentation, as do human subjects, which allows close contact between the maternal circulation and the fetal circulation (21). Second, CsA-induced acute nephrotoxicity in adult rabbits exhibits close similarities to CsA-induced renal side effects among human subjects (22,23). Third, the kidneys of rabbit pups exhibit anatomic and functional characteristics similar to those of human neonatal kidneys (24).…”
mentioning
confidence: 90%
“…Microvacuolization, observed here, has been described as a characteristic of acute CsA-induced nephrotoxicity in rats 22,23) and rabbits. 24) These results indicate that nephrotoxicity appears to increase with dose of CsA in rats, and remarkable acute nephrotoxicity model was established for the high-dose group.…”
Section: Resultsmentioning
confidence: 63%
“…Eighteen male wistar rats weighting 200 AE 20 g were purchased from the Department of Laboratory Animal Science at the Peking University Health Science Center, and were allowed to acclimatize for 3 d. Six rats were housed in one cage and had free access to water and food. They were maintained under standard conditions: 12 h light-dark cycle, [22][23][24] C, and 50-60% humidity. In the present study, all experiments were performed under the guidelines of the Experimental Laboratory Animal Committee of Peking University Health Science Center and were in strict accordance with the principles and guidelines of the China National Institutes of Health Guide for the Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%
“…CyA-induced nephrotoxicity can be either acute or chronic in nature [17, 23]. Clinically, acute CyA toxicity is characterized by a decrease in glomerular filtration rate and renal blood flow that is reversible by reduction of the administered dose or withdrawal of the drug [4, 36, 41]. However, in the chronic setting, the morphological alterations of CyA nephrotoxicity are confined to the tubular and interstitial space [23], with the tubular lesions predominating within the proximal tubule [17, 23].…”
Section: Introductionmentioning
confidence: 99%